Comprehensive evaluation of two different inoculums in MFC with a new tin-coated copper mesh anode electrode for producing electricity from a cottonseed oil industry effluent - Taskan, Ergin; Ozkaya, Bestamin; Hasar, Halil (Wiley-Blackwell, 2016)
We evaluated a new electrode material for its capacity to generate electricity by using a cottonseed effluent in two microbial fuel cells (MFCs). Tin-coated copper (Sn-coating Cu) mesh and platinum-coated titanium were used as anode and cathode electrode materials, respectively. For a startup period that allowed slow-growing electro-active bacteria to form biofilms on the anode electrode, inoculums were supplied from anaerobic digester sludge (ADS) and estuary sediment (ES). The ADS-inoculated MFC successfully achieved maximum power density of 160 mW/m(2), whereas ES-inoculated MFC had a maximum power density of 59 mW/m(2). Maximum columbic efficiencies for ADS and ES were 12.8% and 5.6% and the corresponding COD removal efficiencies were 66.6% and 53.6%, respectively. A PCR-DGGE analysis showed that the anode surface in ADS-inoculated MFC has more groups of bacteria than that in ES-inoculated MFC. The kinetic performances of MFCs evaluated by using the Nernst-Monod equation showed that maximum current density (J(max)) increased to around 1.62 A/m(2) in the ADS-inoculated MFC and 1.06 A/m(2) in the ES-inoculated MFC. (c) 2015 American Institute of Chemical Engineers Environ Prog, 35: 110-116, 2016
Keywords: microbial fuel cell (MFC); kinetics; cottonseed oil industry; electrode material; power generation